Pengaruh Pembelajaran Tatap Muka Terbatas Terhadap Minat Belajar Kewirausahaan Siswa SMK Plus Umar Zahid - Shanti nugroho Sulistyowati; Fahimul Amri (Universitas Negeri Surabaya, 2022)
The significance of entrepreneurship education stems from the fact that the number of entrepreneurs is one indicator of a country's level of prosperity/progress, but since Covid-19 was declared a national disaster in Indonesia, the learning process shifted to an online format. The online learning process cannot be separated from the pros and cons, the use of online-based learning media, both synchronous and asynchronous online, including the emergence of new problems in online learning, namely learning loss or the loss of opportunities to gain knowledge and skills. The goal of this study was to explain how limited face-to-face learning affected students' interest in learning entrepreneurship at SMK Plus Umar Zahid. This type of research is quantitative with a simple linear regression analysis technique. This type of research is quantitative with a simple linear regression analysis technique. According to the findings of the study, limited face-to-face learning has an effect on entrepreneurship learning interest.